Layer-specific targeting of direction-selective neurons in the zebrafish optic tectum - Gabriel, Jens Peter; Ryu, Soojin; Bollmann, Johann (Neuron, 2012)
Summary Direction selectivity (DS) is an important neuronal property in the visual system, but how DS is generated beyond the retina remains controversial. Here, we report a close correspondence between the preferred direction (PD) and the morphology of DS cells in the optic tectum. Ca2+ imaging in cells expressing the genetically encoded Ca2+ indicator GCaMP3 and multiphoton-targeted patch-clamp recordings allowed us to compare structure and function in single neurons. The arbors of differently tuned cell types showed stereotypic differences in shape and laminar profile within the tectal neuropil. Excitatory synaptic inputs were directionally tuned and matched the PD of spike output in these cells, while inhibitory inputs were selective for nonpreferred directions. Functional Ca2+ imaging in afferent axons showed a matching laminar distribution of DS presynaptic activity. Hence, different directions are represented in different layers, which suggests a simple mechanism for how tectal neurons acquire directional tuning in a nascent circuit.
Gesehen am 04.10.2018